Chicken Heads as a Promising By-Product for Preparation of Food Gelatins - Gál, Robert; Mokrejš, Pavel; Mrázek, Petr; Pavlačková, Jana; Janáčová, Dagmar; Orsavová, Jana (Molecules (Basel, Switzerland), 2020)
Every year, the poultry industry produces a large number of by-products such as chicken heads containing a considerable proportion of proteins, particularly collagen. To prepare gelatin is one of the possibilities to advantageously utilize these by-products as raw materials. The aim of the paper was to process chicken heads into gelatins. An innovative method for conditioning starting raw material was using the proteolytic enzyme. Three technological factors influencing the yield and properties of extracted gelatins were monitored including the amount of enzyme used in the conditioning of the raw material (0.4% and 1.6%), the time of the conditioning (18 and 48 h), and the first gelatin extraction time (1 and 4 h). The gelatin yield was between 20% and 36%. The gelatin gel strength ranged from 113 to 355 Bloom. The viscosity of the gelatin solution was determined between 1.4 and 9.5 mPa.s. The content of inorganic solids varied from 2.3% to 3.9% and the melting point of the gelatin gel was recorded between 34.5 and 42.2 °C. This study has shown that gelatin obtained from chicken heads has a promising potential with diverse possible applications in the food industry, pharmacy, and cosmetics.
Keywords: kur domácí; Animals; food applications; Gelatin; Food-Processing Industry; Gels; Chickens; průmysl zpracování potravin; Food; Collagen; Time Factors; časové faktory; enzyme technology; by-products; kolagen; gelatin; proteasy; hlava; Peptide Hydrolases; sustainability; chicken heads; gely; želatina; innovative process; viskozita; zvířata; Head; Viscosity; extraction; potraviny